Testes de estrutura ótima de capital em empresas brasileiras: o efeito de liquidez, desempenho do mercado acionário e assimetria de informação nas decisões de financiamento - Pereira Neto, Allemander Jesus (2006)
This paper explores, through empirical tests, which one of the two main theories concerning optimal capital structure choice, the Static Trade-off Theory (STT) or the Pecking Order Theory( POT) best explains the financing decisions made by Brazilian companies. Additionally, the effects of information asymmetry, market performance and liquidity on these decisions were studied. Data for Brazilian public companies within the period of 1995 to 2005 is used, testing two representative models of the Static Trade-off Theory (STT) and the Pecking Order Theory (POT). Initially, the broad panel of companies is tested and subsequently tests are carried out in control groups exploring the effects of market performance and liquidity, share liquidity and information asymmetry. The results obtained are indicative that the Pecking Order Theory, in its semistrong form, best explains the capital structure choice of Brazilian companies, whereby internal cash generation, operational and financial indebtedness are used as primary sources of funds. The issuance of shares by companies is used, however at low levels. The empirical tests carried out in the control groups suggest that market and share liquidity are influence factors in the companies propensity to issue stocks, as well as information asymmetry. Based on the data analyzed, market performance appears to have little influence on the companies willingness to issue shares as a source of funding, without however, distinguishing among public or private lacements.